Correction: Silver-mediated direct phosphorylation of benzothiazoles and thiazoles with diarylphosphine oxides. Issue 94 (3rd November 2015) - Zhang, Hui-Jun; Lin, Weidong; Wu, Zhengjian; Ruan, Wenqing; Wen, Ting-Bin
Abstract : Correction for 'Silver-mediated direct phosphorylation of benzothiazoles and thiazoles with diarylphosphine oxides' by Hui-Jun Zhang et al., Chem. Commun., 2015, 51, 3450–3453.